The influence of interpersonal relationships on Mary’s psychological transformation: A Freudian personality dynamic in The Secret Garden (1911) - Alysa Marchelin; Leni Marlina (Researcher and Lecturer Society, 2026)
This study investigates how Mary Lennox’s interactions with other characters influence the dynamics of the id, ego, and superego in Frances Hodgson Burnett’s The Secret Garden (1911), drawing on Sigmund Freud’s psychoanalytic theory. Previous studies on The Secret Garden have primarily emphasized ecocritical, pastoral, and socio-cultural perspectives, while limited attention has been paid to the role of interpersonal relationships in shaping Mary’s psychological transformation through Freudian personality dynamics. Addressing this gap, the present study employs a qualitative descriptive approach using close reading to examine textual evidence related to Mary’s interactions with Martha, Dickon, and Colin. The analysis was conducted systematically through textual identification, coding, categorization, and thematic interpretation based on Freud’s concepts of the id, ego, and superego. The findings reveal that Mary’s early behavior is predominantly driven by the id, reflected in her selfishness, impulsiveness, and emotional instability. However, continuous interactions with supportive characters gradually strengthen the ego, enabling her to balance instinctive desires with social reality. Simultaneously, the superego develops through her increasing empathy, moral awareness, and sense of responsibility toward others. The study demonstrates that personality transformation occurs through the dynamic interaction of psychic structures rather than through isolated psychological change. Ultimately, Burnett’s novel illustrates how emotional growth and moral development emerge through social interaction, environmental influence, and the reconciliation of instinct, reason, and morality.